Study of Electric Field Emissions in Wireless Energy Transfer - Baikova, Elena (2021)
The thesis focuses on the study of the electrical component of the electromagnetic field, radiated by the wireless energy transfer system into the adjacent environment. The wireless energy transfer and the wireless data transfer are studied simultaneously, focusing on the appropriate wireless communication channel between the transmitter and the receiver, so to make that channel improved. An implementation of a wireless energy transfer experimental prototype that operates simultaneously with a wireless data transmission is assembled. A computational application that allows tuning the operational frequency of the prototype to correspond to the resonant mode operation is developed.